Analysis of Rhodamine B Levels in Cotton Candy Circulated in Makassar City - Ahsyaf, Dhela Ainun Qalbi; Aminah, Aminah; Kisra, Andi Trihadi Kusuma (Universitas Muslim Indonesia, 2023)
Rhodamine B is a synthetic dye used as a textile dye. It is prohibited as a Food Additive because it can irritate the digestive tract, poison, and even cause cancer and death. The research was to see if there were any Rhodamine B deposits of cotton candy in Makassar. This test used five samples. The methods used in testing are TLC and spectrophotometry UV-Vis. All five samples' test results show no stain was formed (negative). UV-Vis spectrophotometry test on a 553 nm length acquired data of Rhodamine B levels in a row as follows: first sample of cotton candy = 0.005%, sample 2 of cotton candy = 0.001%, sample 3 of cotton candy = 0.0008%, sample 4 of cotton candy = 0.003%, and sample 5 of cotton candy = 0.0009%. They concluded that all five samples identified contained Rhodamine B synthesized dye to a minimal degree of the cotton candy sample distributed in Makassar.